The Influence of Leverage, Company Size, And Asset Structure On The Value Of Mining Companies Listed On The Indonesia Stock Exchange - I Wayan Krisna Yudha; I Gde Kajeng Baskara (International Journal of Economics, Management and Accounting, 2025)
Firm value reflects investors’ perception of a company’s success, often associated with stock price. An increase in firm value can serve as a positive signal for investors, indicating promising future prospects. This study aims to examine and explain the influence of leverage, company size, and asset structure on the value of mining companies listed on the Indonesia Stock Exchange. The study involves a sample of 77 mining companies for the period 2020–2024. Data was collected using a non-participant observation method. The analytical technique employed is multiple linear regression analysis. The results show that leverage has a positive and significant effect on firm value, company size has a negative and significant effect on firm value, and asset structure has a positive but insignificant effect on firm value.